2016
DOI: 10.21134/haaj.v16i2.266
|View full text |Cite
|
Sign up to set email alerts
|

Perfiles de consumo de alcohol y tabaco en adolescentes andaluces de primer ciclo de educación secundaria

Abstract: ResumenAdolescence is the stage at which teenagers begin to consume tobacco and alcohol, associating with problems in their maturational development and unhealthy habits that can be difficult to eradicate in adulthood. This descriptive and cross-sectional study was conducted on a sample of 526 students from first cycle of secondary education, with an age between 12 and 15 years old adolescentes consumían alcohol y la mayoría no mostraba dependencia al tabaco. El consumo de estas sustancias aumentaba con la eda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Keeping in mind some of the above variables, in the study by Chacón et al [45], tobacco and alcohol use profiles were found, in which smoking was linked to improper use of alcohol and illegal drugs. Use of alcohol has also been associated with having friends who drink and smoke.…”
Section: Risk and Protection Factors Of Using Alcohol And Tobaccomentioning
confidence: 99%
“…Keeping in mind some of the above variables, in the study by Chacón et al [45], tobacco and alcohol use profiles were found, in which smoking was linked to improper use of alcohol and illegal drugs. Use of alcohol has also been associated with having friends who drink and smoke.…”
Section: Risk and Protection Factors Of Using Alcohol And Tobaccomentioning
confidence: 99%
“…Other community-based survey research in Mexico, however, show findings similar to the current study. For example, Chacón et al (2016) found that alcohol consumption among adolescents in Mexico starts at 12 years old, but it is in the middle and advanced adolescence when there is more acute consumption. Studies consistently show that early onset of alcohol use is associated with numerous adverse outcomes (Stueve & O'Donnell, 2005; Swahn & Bossarte, 2007; Tanaree et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos de este estudio permitieron conocer la situación actual de los estudiantes de Enfermería, donde se observó que la mayoría de los estudiantes aún viven con sus padres, lo cual concuerda con investigaciones previas (Trujillo-Guerrero et al, 2016); en lo concerniente al tipo de consumo se identificó que más de la mitad de la población reportó bajo riesgo, lo que coincide con estudios que indican que más de la mitad tiene un consumo de bajo riesgo; sin embargo, es relevante resaltar que gran porcentaje reporta un consumo de riesgo y perjudicial; estos resultados concuerdan con Alonso-Castillo et al (2018) y con Chacón Cuberos et al (2016). Con respecto al funcionamiento familiar, los resultados reflejaron que gran parte de los estudiantes de Enfermería que participaron perciben un funcionamiento familiar normal; estos resultados son similares a los reportados en otros estudios donde han encontrado que la mayoría perciben un funcionamiento familiar normal (Musitu Ochoa, Suárez Relinque, del Moral Arroyo, & Villarreal González, 2015).…”
Section: Materiales Y Métodosunclassified